Imaging Findings in Neonates With Congenital Pyriform Sinus Fistula: A Retrospective Study of 45 Cases - Li, Li; Zhao, Dong-Ji-Hui; Yao, Tao-Yue; Xiang, Yong-Hua; Liu, Hong; Ma, Qiu-Hong; Jin, Ke; He, Si-Ping (Frontiers in Pediatrics, 2021)
Background: Congenital pyriform sinus fistula (CPSF) is a rare branchial cleft deformity. The characteristics and management of CPSF in neonates are different from those in children or adults, and a comprehensive understanding of the imaging features of neonatal CPSF can facilitate its preoperative diagnosis. Thus, the aim of this study was to summarize the ultrasonography (US) and CT imaging findings of CPSF in neonates. Methods: Forty-five full-term neonates with CPSF, confirmed by pathology after surgical resection from January 2012 to October 2020, were included in this retrospective study. All patients underwent preoperative cervical US and contrast-enhanced CT examinations, and the imaging findings were analyzed. Results: Forty-six cervical cystic masses were found in 45 neonates, including one case with bilateral lesions, three cases with lesions on the right side, and 41 cases on the left side. Both US and CT detected neck abnormality among all cases, while the diagnostic accuracy of US (15/46, 32.6%) was lower than that of CT (42/46, 91.3%). Moreover, CT showed significantly higher detection rates of intralesional air bubbles, involvement of the ipsilateral thyroid, deviation of the airway, and expansion into the mediastinal and retropharyngeal space compared with the US. As the age increased, it was more likely to present some features including the absence of air-containing, thick cyst wall, and poorly defined border (ρ <0.05). Conclusion: CPSF in the neonates showed distinctive imaging findings on contrast-enhanced CT scan, which provides important supplementary information for the diagnosis of CPSF after the initial US examination.